2014
DOI: 10.1093/treephys/tpu089
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of nocturnal water loss: a synthesis of regulating factors and implications for capacitance, embolism and use in models

Abstract: Total daily water use is a key factor influencing the growth of many terrestrial plants, and reflects both day-time and nocturnal water fluxes. However, while nocturnal sap flow (En) and stomatal conductance (gs,n) have been reported across a range of species, ecosystems and microclimatic conditions, the regulation of these fluxes remains poorly understood. Here, we present a framework describing the role of abiotic and biotic factors in regulating En and gs,n highlighting recent developments in this field. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
121
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(126 citation statements)
references
References 70 publications
3
121
2
Order By: Relevance
“…Zeppel et al [49] used data from many ecosystems to examine the abiotic factors that may affect the S dn and found that S dn was higher in broad-leaved compared with needle-leaved plants and in tropical compared with temperate species. Our study also demonstrates that S dn accounted for 2.71%-12.56% (Q. acutissima) and 8.00%-24.29% (C. lanceolata) of the whole-day sap flow throughout the study period, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zeppel et al [49] used data from many ecosystems to examine the abiotic factors that may affect the S dn and found that S dn was higher in broad-leaved compared with needle-leaved plants and in tropical compared with temperate species. Our study also demonstrates that S dn accounted for 2.71%-12.56% (Q. acutissima) and 8.00%-24.29% (C. lanceolata) of the whole-day sap flow throughout the study period, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, P ar and V pd explained the greatest amount of variation in daytime sap flow of Q. acutissima and C. lanceolata, respectively. In addition, V pd and soil water content (S wc ) were the abiotic drivers of nocturnal sap flow [49]. Causally, V pd is also used to determine whether S dn is related to either nocturnal transpiration or stem refilling [16,19,52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggest using nighttime stomatal conductance values (e.g. Zeppel et al, 2014). However, minimum stomatal conductance values measured during the day are considerably lower than measured nighttime values (Walden-Coleman et al, 2013).…”
Section: Minimum Stomatal Conductance Gmentioning
confidence: 99%
“…First, night transpiration may lower leaf temperature by evaporative cooling, thereby decreasing carbon losses through dark respiration (42). Night water fluxes may otherwise have beneficial roles in nutrient transport (43) and O 2 supply to the xylem parenchyma (16,44). Incomplete stomatal closure at night may also accelerate photosynthesis resumption at sunrise (45), but this has not always been observed (46).…”
mentioning
confidence: 99%